2010
DOI: 10.1179/026708410x12593178265823
|View full text |Cite
|
Sign up to set email alerts
|

Microstructure formation and properties of HVOF sprayed NiTi coatings prepared from amorphous/nanocrystalline NiTi powders

Abstract: NiTi alloys were sprayed on AISI 1045 steel substrate using high velocity oxyfuel process. In this regard, amorphous/nanocrystalline NiTi powders were used as feedstock. The phase composition and microstructure of the coatings were examined by X-ray diffraction and scanning electron microscopy. The results indicated that B2-NiTi (austenite phase), Ni 4 Ti 3 , Ni and NiTiO 3 were present in the coatings. In addition, all sprayed coatings showed high microhardness values (.588 HV0?3). Further investigations show… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
14
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 10 publications
(15 citation statements)
references
References 31 publications
(79 reference statements)
1
14
0
Order By: Relevance
“…The formation of Ni 4 Ti 3 phase as a metastable precipitate has been previously reported during air plasma spraying of NiTi alloys [15]. The Ni phase is formed either due to crystallization of amorphous phase or preferential oxidation of Ti element during the spraying process [12,15]. Formation of Ni has been previously reported in HVOF spraying of NiTi intermetallic powders [11,12].…”
Section: Characterization Of Powders and Coatingsmentioning
confidence: 94%
See 4 more Smart Citations
“…The formation of Ni 4 Ti 3 phase as a metastable precipitate has been previously reported during air plasma spraying of NiTi alloys [15]. The Ni phase is formed either due to crystallization of amorphous phase or preferential oxidation of Ti element during the spraying process [12,15]. Formation of Ni has been previously reported in HVOF spraying of NiTi intermetallic powders [11,12].…”
Section: Characterization Of Powders and Coatingsmentioning
confidence: 94%
“…1. A broad diffraction peak at the Bragg angles of 41-45 • indicates the presence of an amorphous/nanocraystalline phase in feedstock powders [12][13][14][15]. The studies of HVOF coating revealed that the peaks belonging to NiTi (austenite phase), Ni 4 Ti 3 , Ni and also NiTiO 3 exist in the respective XRD pattern.…”
Section: Characterization Of Powders and Coatingsmentioning
confidence: 95%
See 3 more Smart Citations